2008
DOI: 10.2975/31.3.2008.194.200
|View full text |Cite
|
Sign up to set email alerts
|

Multi-modal weight control intervention for people with persistent mental disorders.

Abstract: Obesity, a major problem worldwide, is more prevalent among people with schizophrenia. This study examined the effect of behavior intervention, nutritional information and physical exercise on the body mass index (BMI) and weight of people who were hospitalized with persistent DSM-IV schizophrenia and schizoaffective disorders. Fifty nine inpatients with a BMI greater than 25 participated, (28 intervention group; 31 control group). Significant reductions in BMI and weight were observed in the intervention grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 26 publications
3
52
0
Order By: Relevance
“…(Melamed et al, 2008; Chen et al, 2009; Chwastiak et al, 2009) Comprehensive lifestyle therapies in the general community, however, have shown weight loss of 2 to 10 kilograms (i.e., 4 to 22 pounds) over 10 to 20 weeks, but weight regain over a one-year period. (Hensrud, 2001)…”
Section: 1 Discussionmentioning
confidence: 99%
“…(Melamed et al, 2008; Chen et al, 2009; Chwastiak et al, 2009) Comprehensive lifestyle therapies in the general community, however, have shown weight loss of 2 to 10 kilograms (i.e., 4 to 22 pounds) over 10 to 20 weeks, but weight regain over a one-year period. (Hensrud, 2001)…”
Section: 1 Discussionmentioning
confidence: 99%
“…The combined effect of behavioral intervention, nutritional information, and physical exercise was investigated in a study of people with schizophrenia and body mass index (BMI) exceeding 25. The 3-month intervention program showed significant reduction in weight and BMI, which lasted 12 months (159). Intriguingly, weight reduction was gradual, with increasing weight loss as the program progressed, in contrast to weight reductions patterns in diet programs in healthy individuals, where there is often a larger reduction of weight early on.…”
Section: Intervention Studiesmentioning
confidence: 99%
“…Its results are similar to those reported by other studies of weight loss interventions, which found a mean loss of 4.3±5.6 pounds (5). Participants in the RENEW program had maintained their weight loss at six months; other studies indicate that individuals with serious mental illness who have participated in weight loss programs have maintained their weight loss for up to one year (8,9). A subgroup of RENEW participants lost 5% to 10% of body weight, an achievement that is associated with important health benefits such as reduced risk of diabetes and high blood pressure (10).…”
Section: Discussionmentioning
confidence: 99%